Chemistry ([S.l.] : Knowledge Books & Software Multimedia, 1999)
Contains chemical reactions and stoichiometry that will constructing models from molecules. Atom structure and models made
System requirements: Windows 3.X, Windows 95, 98, Windows NT 4.0, 486 SX or better, or Pentium, CD ROM double-spin or better, 4 MB RAM, VGA Card
Keywords: Chemical reactions; Atomic theory